Mountains of Experience Interdisciplinary, Intercultural, International - Volume One - Lanier, Parks (Appalachian State University, 1989)
This volume of the Journal of Appalachian Studies Association includes contributions from various disciplines by Parks Lanier, Jr.; Marilou Awiakta; C. Clifford Boyd, Jr.; Ricky L. Cox; Betty Smith; James E. Byer; Edgar H. Thompson; Teresa Wheeling; Paul J. Weingartner, Dwight Billings, and Kathleen M. Blee; Nelda Knelson Daley; Roberta McKenzie; Barry Elledge; Benita J. Howell; Rodger Cunningham; Laurie Lindberg; and Clyde H. Ray.